Pedra, papel e tesoura: direitos humanos, redução de danos e política pública na Cracolândia de São Paulo - Collier, Tamara Neder (2020)
This research aims to contribute to the reflection on the use of psychoactive agents in capitalist society from the perspective of social ontology. We present a critical reading of the social reality that permeates thesocial conditions of psychoactive use in the context of production and consumption and how the prohibitionist ideology dictated by the War on Drugs establishes stigmas in relation to the psychoactive user and strengthens the construction of a social imaginary based on culture of fear. This dissertation defends harm reduction as a collective health paradigm and its object of study is the public policy aimed at people who use crack in the territory of São Paulo's Cracolândia from 2010 to 2020, in particular the Harm Reduction Program SAE Campos Elísios, whose guidelines are established by the Municipal HIV / STI Program of São Paulo. We make our analysis about the realization of the social rights of people who use psychoactive from the perspective of the harmreduction and Human Rights paradigm, emphasizing the importance of social movements in the construction of coping strategies and resistance to the violation of human rights imposed by public policy based on the War on Drugs